The chronicle of transposition hysterectomy specimens with clinical and histopathological correlation: a three year study - Vasudeva, Shalini; Thapa, Ragini (International Journal of Research in Medical Sciences, 2020)
Background: Hysterectomy is the commonest gynaecological surgery which involves surgical removal of the uterus. Hysterectomy and microscopic evaluation of the samples are still the only ways of definite diagnosis. Early evaluation in the perimenopausal and postmenopausal women is essential to confirm the exact nature of the lesion and to rule out malignancy. Methods: After obtaining institutional Ethical Committee approval and written informed consent, hysterectomy specimens of 200 patients with abnormal uterine bleeding were studied for histopathological examination during the period of June 2016 to June 2019 from tertiary care centre and hospital. Results: Mean age of cases was 22-80 years. The common significant pathological lesions were adenomyosis in 55(27.2%) cases, leiomyoma in 49(23.2%) cases, leiomyoma with adenomyosis in 22(9.3%) cases, CIN1 in 6 cases (3.0%), serous cystadenoma of ovary in 5(2.4%) cases, endometrial polyp in 5(2.4 %) cases, carcinoma of cervix in 4 (2.2%) cases, carcinoma of ovary in 3(2.4%) cases and carcinoma of endometrium in 1 (0.6%) cases. The correlation of HP findings of hysterectomy specimens with cervical biopsy findings was 79.4% and that with endometrial biopsy findings was 100%. The cervico-vaginal cytology (Pap smear) findings of 93.2 % cases were in agreement with HP findings of cervix in hysterectomy specimens. Conclusions: This study provides baseline data to follow the trend of the hysterectomy and put insight into the pattern of complaints .The final HP findings of the hysterectomy specimens correlates well with the preoperative clinical diagnosis, ultrasonography, cervical biopsy, endometrial biopsy, Pap smear and tumour marker level findings.